Problematic Social Stratification Experienced by Aibileen Clark in Tate Taylor’s The Help (2011) Movie Script - Fennyta Diva Fadilla; Hariyono (Menulis: Jurnal Penelitian Nusantara, 2025)
This paper would like to examine the matter of problematic social stratification experienced by Aibileen Clark in Tate Taylor’s The Help (2011) movie script. The Help is a movie tells about the character named Aibileen Clark that faces such racial discrimination as a maid in America around 1960s. This movie is crucial to be a theme of a thesis because it speaks about such a system that restricted human freedom as specially in applying certain freedom. Trough qualitative method, this study employs close reading as technique of data collection and winnowing as technique of data analysis. The analysis results to ideas of Aibileen Clark experiences problematic social stratification of inequalities which unequally distribute societal resources (such as income and power) with the most privileged individuals and families enjoying a disproportionate share. Aibileen even feels hesitant to speak about her opinions regarding white people, not only because of laws but also because of differences in power. In conclusion, Aibileen Clark clearly experiences social inequality in economy, social status, and political power, and her story reflects the struggles of many Black women in American history through her voice.